(E)-2-Methoxy-N′-(4-nitrobenzylidene)benzohydrazide - Ban, Hong-Yan (International Union of Crystallography, 2009)
In the title compound, C(15)H(13)N(3)O(4), the molecule exists in a trans configuration with respect to the methylidene unit. The dihedral angle between the two benzene rings is 6.8 (2)°. The C—N—NH—C torsion angle is 3.4 (3)°. The molecule possesses an intramolecular N—H⋯O hydrogen bond. In the crystal structure, adjacent molecules are linked through intermolecular C—H⋯O hydrogen bonds, forming dimers